Assisted Coral Reproduction in the Dominican Republic: A Successful Story to Replicate in the Caribbean - Sellares-Blasco, Rita I.; Villalpando, Maria F.; Guendulain-García, Sergio D.; Croquer, Aldo (Frontiers in Marine Science, 2021)
Coral assisted fertilization, larval rearing and recruit propagation success in significant ecological scales, largely depend on scaling up and replicating these efforts in as many regions as possible. The Dominican Foundation for Marine Studies (FUNDEMAR) has become a pioneer of these efforts in the Dominican Republic, being the first institution to successfully implement coral sexual reproduction techniques in the country and establishing the first mobile larvae culturing facility. Here we share our perspective on three main components behind the success of FUNDEMAR’s program: (1) a self-sustainable program in alliance with local and international organizations, (2) the design and construction of the first Coral Assisted Reproduction Laboratory in the country, and a (3) clearly defined scalable structure for outcome performance. Two years after program implementation, FUNDEMAR has successfully produced an annual regional coral spawning prediction calendar, cultured seven coral species, and seeded over 4,500 substrates with more than 268,200 sexual coral recruits in approximately 1,880 m 2 reef areas. Here, we provide a detailed description of a fully functional assisted coral reproduction program, including the lessons learned during its implementation as well as a series of specific solutions. We hope this work will help and inspire other countries and small institutions to replicate FUNDEMAR’s coral assisted reproduction program components and contribute to the expansion of sexual coral restoration efforts in the Caribbean.